Chitin Extraction and Content Measurement in Magnaporthe oryzae - Xinyu Liu; Zhengguang Zhang (Bio-Protocol, 2017)
Chitin is a linear polysaccharide composed of β (1→4)-linked N-acetylglucosamine (GlcNAc) residues. In fungi, chitin is an important component of the cell wall. Here, we provide a protocol to measure the chitin content of fungal cells using Magnaporthe oryzae as an example.